Rancang Bangun Aplikasi Monitoring Penanganan Gangguan Teknis Jaringan Tegangan Rendah (JTR) Berbasis Android Pada PT. PLN (PERSERO) APJ Surabaya Utara - Putra, Tegar Muharyana; Sutanto, Teguh; Widodo, Arifin Puji (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
PT. PLN (Persero) to provide services in handling technical problems of low voltage network must have a standard time for acting as executor outsourced at PT. Haleyora Power. To monitor the performance of third parties are still using manual recording of which has a risk response time and handling time is always reported good, but complaints about delays in response time and handling time is still very much. This led to the performance of a partner company of PT. PLN (Persero) can be monitored and lead to poor image PT. PLN (Persero) in the eyes of customers.To overcome these problems is developed monitoring applications handling low voltage networks based on Android which has several important features: monitoring functions are handled by the short message service (SMS) supervisor, dashboard map, monthly performance reports in the form of charts and PDF files.The trial results were made known that the application can produce interference notification, response time, time management, SMS monitoring supervisor. For the report, the application can generate reports such as monthly performance dashboard, dashboard maps and performance reports in a PDF file. It can be concluded from the test results are known 1% response time is not standards-compliant, 99% has met the standard 45 minutes. For a time there was a 50% handling that is not standards-compliant, 50% has met the standard of 120 minutes.